The Evaluation of User Interface and User Experience in the New Student Admission System : Case Study: New Student Admission System at UPN Veteran Jawa Timur - Alam, Fajar Indra Nur; Harya, Gyska Indah (Information Technology International Journal, 2025)
In the current digital era, information technology plays a crucial role in various aspects of life, including education. One notable application is the digital-based new student registration system, designed to replace manual methods that are time-consuming, error-prone, and inefficient. While digital systems aim to streamline the registration process, their success is heavily reliant on the quality of their User Interface (UI) and User Experience (UX). Poor UI/UX design can lead to user confusion, frustration, and registration failure. This study evaluates the UI and UX of the new student registration system implemented by UPN Veteran Jawa Timur. Using usability testing and heuristic evaluation, the research identifies challenges in navigation and interface design that hinder user satisfaction. The findings offer actionable recommendations to improve system efficiency and user-friendliness. This study not only contributes to enhancing the registration process for UPN Veteran Jawa Timur but also serves as a reference for similar systems aiming to optimize their UI/UX design.